A crystallographic study of Bis[S-benzyl-5-bromo- 2-oxoindolin-3- lidenemethanehydrazonthioate] disulfide solvated with dimethylsulfoxide / Mohd Abdul Fatah Abdul Manan ... [et al.] - Abdul Manan, Mohd Abdul Fatah; M. Tahir, M. Ibrahim; Karen A., Crouse; Fiona N.-F., How; David J., Watkin (Research Management Institute, 2012)
The crystal structure of the title compound has been determined. The compound crystallized in the triclinic space group P -1, Z = 2, V = 1839.42(18) Å3 and unit cell parameters a = 11.0460(6) Å, b = 13.3180(7) Å, c = 13.7321(8) Å, α = 80.659(3)°, β = 69.800(3)° and γ = 77.007(2)° with one disordered dimethylsulfoxide solvent molecule with the sulfur and oxygen atoms are distributed over two sites; S101/S102 [site occupancy factors: 0.6035/0.3965] and O130/O131 [site occupancy factor 0.3965/0.6035]. The C22-S21 and C19-S20 bond distances of 1.779(7) Å and 1.788(8) Å indicate that both of the molecules are connected by the disulfide bond [S20-S21 2.055(2) Å] in its thiol form. The crystal structure reveals that both of the 5-bromoisatin moieties are trans with respect to the [S21-S20 and C19-N18] and [S20-S21 and C22-N23] bonds whereas the benzyl group from the dithiocarbazate are in the cis configuration with respect to [S21-S20 and C19-S44] and [S20- S21 and C22-S36] bonds. The crystal structure is further stabilized by intermolecular hydrogen bonds of N9-H35⋅⋅⋅O16 formed between the two molecules and N28-H281⋅⋅⋅O130, N28-H281⋅⋅⋅O131 and C41-H411⋅⋅⋅O131 with the solvent molecule.